Pengaruh Corporate Social Responsibility terhadap Citra Perusahaan di PT Telekomunikasi Indonesia, Tbk. - Naufalia, Viani (Program Studi Pendidikan Ekonomi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Prof. DR. HAMKA, 2016)
This study aimed to determine the effect of corporate social responsibility to corporate image at PT. Telekomunikasi Indonesia, Tbk in North Jakarta. The population of this study is all Telkom customers who visited Plasa Telkom in North Jakarta during the study period. The sample of this study amounted to 67 customers who taken uses incidental sampling technique.This research uses the associative quantitative research method.After the data have the same characteristics and normal distribution based on normality and homogeneity test, followed by analysis of variance (ANAVA). Based on the results of linear regression calculations obtained Å¶ = 30.14 + 0.598 (x) and the calculation of ANAVA obtained Fhitung < Ftabel (1.127, 1.691). Hypothesis testing is done by calculating the correlation of the Pearson product moment and obtained rxy=0.615, it shows the influence of corporate social responsibility to corporate image at PT. Telekomunikasi Indonesia, Tbk in North Jakarta is Strong in accordance with the interpretation criteria in Table Interpretation of Correlation Coefficients. Therefore, the results of this study can be concluded that there is an influence between corporate social responsibility to corporate image at PT. Telekomunikasi Indonesia, Tbk in North Jakarta.